PERAN KEPUASAN KERJA MEMEDIASI KOMPENSASI TERHADAP KINERJA (STUDI PADA PERUSAHAAN TENUN WIDHI SRI-KLUNGKUNG) - gde sarmawa (Jurnal Ilmiah Manajemen & Bisnis, 2016)
This study aimed to determine the role of employee satisfaction in mediating the compensation to employee performance carried on weaving company Widhi Sri, by involving all employees of the company totaling 61 persons as respondents. This study was conducted with a census approach, therefore, it involved the whole company's employees as respondents. The collecting of the data in this study was conducted by distributing questionnaires to respondents. The data of the study were processed by the method of Partial Least Square (PLS), through a program named SmartPLS 2.0 M3, at the significance level of 0.05 (5%). The results of this study found that compensation and employee satisfaction provided a positive and significant influence on employee performance. The effect occurred by compensating for the employee performance without the involvement of employee satisfaction was at 0.315, it was lower than the influence caused by compensation to employee performance by involving employee satisfaction, which was equal to 0.640. Therefore, it meant that employee satisfaction was able to mediate compensation to employee performance.